Burnout syndrome among critical care nursing professionals / incidência da Síndrome de burnout em profissionais de enfermagem atuantes em unidade de terapia intensiva - Silva, Ana Paula Farias; Carneiro, Lucilla Vieira; Ramalho, Juliana Paiva Goes (Revista de Pesquisa Cuidado é Fundamental Online, 2021)
Objective: This study aimed at assessing the incidence of Burnout Syndrome among nursing professionals working in the intensive care unit of a public hospital in João Pessoa city, Paraíba State, Brazil, and analyzing the main factors causing this syndrome. Methods: This research with a quantitative approach was performed with both nurses and nurse technicians working in an intensive care unit. Twenty-five professionals with an average age of 37 years old participated in the study, most of them being females working in the area for 18 years on average. Results: Professionals working in hospitals are exposed to different occupational stressors that directly affect their well-being, such as long working hours and constant contact with pain, suffering, and death. Conclusion: From the study results, it was possible to verify the importance of workers' mental health to obtain good professional performance and provide patients with quality care. <!-- Start Crossmark Snippet v2.0 --> <!-- End Crossmark Snippet -->